2022
DOI: 10.1007/s11469-022-00766-5
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ Continuum and Categorical Beliefs, Help-seeking Intentions, and Stigma Towards People Experiencing Depression or Schizophrenia

Abstract: The present study investigated the relationships between continuum and categorical beliefs, stigma, and help-seeking in response to vignettes depicting depression and schizophrenia. Participants were 193 adolescents aged 13-18 years. Results showed no relationships between continuum beliefs and stigma or help-seeking intentions for the depression vignette when controlling for other predictors. Stronger categorical beliefs were associated with greater social distance, and endorsement of dangerousness, avoidance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…The present study explored the effect of continuum beliefs on the public stigma of depressive disorders and found that after emphasizing the continuum view of depressive disorders, the continuum beliefs increased and the public stigma decreased in support of H 1 . This is in line with the ndings of a previous study [23] . However, the small effect size of the results may be because this study used a textual intervention and a weaker experimental intervention, which made it di cult for the subjects to form a common in-group identity.…”
Section: Resultssupporting
confidence: 93%
“…The present study explored the effect of continuum beliefs on the public stigma of depressive disorders and found that after emphasizing the continuum view of depressive disorders, the continuum beliefs increased and the public stigma decreased in support of H 1 . This is in line with the ndings of a previous study [23] . However, the small effect size of the results may be because this study used a textual intervention and a weaker experimental intervention, which made it di cult for the subjects to form a common in-group identity.…”
Section: Resultssupporting
confidence: 93%
“…However, studies rarely mentioned how representativeness was achieved, for instance, via quota sampling or probability sampling; therefore, this information is not included in Table 1 . Seven studies examined (undergraduate) students, seven used Amazon Mechanical Turk (MTurk) samples, and three investigated adolescents [ 51 , 70 ], or mental health professionals [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…It should also be noted that all webpages targeting young people presented continuum conceptualisations. This is despite there being limited research examining the link between continuum conceptualisations and stigmatising attitudes among young people aged up to 18 years (Dolphin & Hennessy, 2017 ; Fernandez et al, 2022 ). Research is needed to explore whether adult findings generalise to an adolescent population and by extension whether the widespread presentation of continuum conceptualisations is justified for this demographic.…”
Section: Discussionmentioning
confidence: 99%